Specialized Supervisory Skills in the Field of Land by People’s Council Deputies - Nguyen , Binh An; Tran, Thi Hai Yen (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Supervision is a fundamental and crucial function of our country’s elected bodies. Since the establishment of the nation, our Party and State have always valued the supervision conducted by the National Assembly and the People’s Councils. According to the 2013 Constitution, the People’s Councils have the function of supervising the adherence to the Constitution and laws at the local level and the implementation of the People’s Council’s resolutions. In recent times, the execution of supervision in the field of land by People’s Council deputies at various levels has seen many positive changes but also presents numerous theoretical and practical issues that need to be addressed. This article focuses on studying the theoretical and practical issues and proposes some solutions to enhance the specialized supervisory skills in the field of land by People’s Council deputies in the coming period.